Pedagogical interventions and their influences on university-level students learning pharmacology-a realist review - Khurshid, Faraz; O’Connor, Elizabeth; Thompson, Rachel; Hegazi, Iman (Frontiers in Education, 2023)
Introduction The knowledge complexity and varied delivery formats in pharmacology education can leave students unprepared in essential pharmacotherapy skills. This significantly influences their ways of thinking and working in clinical environments, resulting in a challenging clinical transition. This need demands pedagogical innovations to strengthen pharmacology education and improve learners’ skills and competencies in pharmacotherapy. This evidence-based realist review aimed to examine the contextual factors and program theories or causal mechanisms crucial for effective pedagogical interventions in pharmacology, seeking to answer the question of ‘what works for whom, under what circumstances, how, and why’. Method The realist synthesis was initiated after retrieving data from Medline (OVID), Cochrane, EBSCO hosted ERIC, SCOPUS, and Embase (OVID) including other sources for additional records. The preliminary analysis enabled the establishment of context, mechanism, and outcome configurations (CMOC) and formulation and refinement of the initial program theory regarding the pedagogical interventions in pharmacology. Data synthesis iteration helped to identify the relevant context and unravel its relationships with underlying causal mechanisms through which said interventions generate outcomes of interest. Results A realist review analyzed 1,217 records and identified 75 articles examining a range of educational interventions from individual efforts to faculty-wide curriculum changes in pharmacology education. The key contexts for pharmacology education were troublesome content, traditional delivery methods, inadequate and limited opportunities for knowledge integration, and application. Active participation in interactive learning, along with enjoyment and motivation, was proposed as a causal mechanism for optimizing cognitive load and achieving positive outcomes. The outcomes of the review include subjective perceptions of improved confidence and satisfaction, objective measurements of high post-test scores. Discussion Pedagogical scaffolding in constructivist learning environments helps students overcome challenges in learning troublesome pharmacology knowledge. Considering the human cognitive system’s processing capacity, these interventions improve learning by effectively using cognitive resources. Innovations that focus on enhancing cognitive load through task construction can also promote positive emotional experiences in students, such as engagement and enjoyment, as explained by flow theory. A constructive learning environment, where the cognitive load is optimized and high flow is achieved, can maximize the impact of pedagogical interventions in pharmacology. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=160441, PROSPERO (CRD42020160441).